The case for universal basic services - Coote, Anna; Percy, Andrew (Polity, 2020)
"The idea that healthcare and education should be provided as universal public services to all who need them is widely accepted. But why leave it there? Why not expand it to more of life's essentials? In this bold new book, Anna Coote and Andrew Percy argue that Universal Basic Services is exactly what we need to save our societies and our planet.
Keywords: Grundversorgung; Infrastruktur; Sozialpolitik; Grundbedürfnisse / (DE-627)091364558 / (DE-2867)10498-5; Sozialpolitik / (DE-627)091390451 / (DE-2867)16545-6; Bildungspolitik / (DE-627)091352045 / (DE-2867)11397-6; Basisgesundheitsversorgung / (DE-627)091349656 / (DE-2867)18894-6; Soziale Wohnungspolitik / (DE-627)091390079 / (DE-2867)18754-1; Personenverkehr / (DE-627)091382904 / (DE-2867)13632-5; Öffentliche Dienstleistung / (DE-627)09138088X / (DE-2867)13303-3; Großbritannien / (DE-627)091364442 / (DE-2867)17374-2; Social policy; Basic needs / Government policy